Prediction of fracture samples of composite materials under the influence of cyclic loading - Buketov, A.V.; Kravtsova, L.V.; Bogdan, A.P. (Bulletin of the Karaganda University. Mathematics Series, 2016)
The article presents the results of an experimental study of polymer composite materials when exposed to cyclic loading. On the basis of experimental data obtained by the analytical parameters of the relationship strength cyclic loading and corresponding deformation of the samples, as well as forecast their destruction taking into account the residual strain.